Evaluation of Fire Prevention and Control System in dr. R. Koesma Regional General Hospital of Tuban Regency in 2021 - Bian Shabri Putri Irwanto; Meirina Ernawati; Indriati Paskarini; Arista Fitri Amalia (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Fires in the workplace can have consequences that adversely affect many parties, both for companies of the workers and the wider community, including institutions such as hospitals. In this research, hospitals are considered to be at high risk of causing fatalities in the event of a fire. The purpose of this research is to evaluate the prevention and control of fire in dr. R. Koesma Hospital Tuban based on the regulation of Minister of Health No.66 of 2016 about Occupational Health and Safety of Hospital. Method: This research is observational research. Data collection was done by interview and observation. The assessment of the evaluation of fire prevention and control is done by using a scoring formula made independently. Result: The evaluation is done on the identification of fire and explosion risk areas as well as on the mapping of high-risk areas of fire and explosion in dr. R. Koesma Hospital based on regulation of Minister of Health No.66 of 2016. The evaluation results on both aspects are 4% out of 6%. The evaluation result of the risk reduction of fire and explosion hazards shows a score of 15% out of 18%. The evaluation result of fire control is 22%. The evaluation result of the fire simulation shows a score of 38% out of 48%. Conclusion: This research concludes that the evaluation results of the fire prevention and control system in dr. R. Koesma Hospital based on regulation of Minister of Health No.66 of 2016 show a score of 83%.